PELATIHAN PERTOLONGAN PERTAMA PADA KECELAKAAN BAGI GURU PENDIDIKAN JASMANI OLAHRAGA & KESEHATAN KABUPATEN BANYUWANGI - Febriyanti, Irma; Mahardika, I Made Sri Undy; Jayadi, Ika; Dewi, Ratna Candra; Ristanto, Kolektus Oky; Wicahyani, Sri (Laksana Olahraga, 2024)
Abstract: First Aid is the first method of providing assistance to people who have had an accident, injury, or illness. Sports injuries can occur due to trauma, force, technical errors, physical limitations, and sports equipment. Sports injuries involve tears in soft tissue such as fascia, muscle fibers, and ligaments. Teachers must have first aid knowledge and skills to deal with these incidents to minimize the increase in the severity of injuries. The method used in this activity is training with demonstrations and discussions as well as practical assistance. Community service activities were carried out in Banyuwangi Regency, with participants being physical education, sports, and health teachers. Through this activity, the Faculty of Sports & Health Sciences at Universitas Negeri Surabaya can provide positive use value in the form of service activities to improve human resources and partners. Participants' responses regarding the implementation of activities had an average rating of 4.4. Keywords: training; first aid; physical education teacher Abstrak: Pertolongan Pertama pada Kecelakaan (P3K) merupakan cara pertama pemberian pertolongan kepada orang yang mengalami kecelakaan, cedera, terluka atau sakit. Cedera olahraga dapat terjadi karena faktor trauma, ruda paksa, kesalahan teknik, keterbatasan fisik dan alat olahraga. Cedera olahraga berupa robek pada jaringan lunak seperti fascia, serabut otot dan ligamen. Guru harus memiliki pengetahuan dan keterampilan pertolongan pertama sehingga mengatasi kejadian tersebut untuk meminimalisir bertambanya tingkat keparahan cedera. Metode yang digunakan dalam kegiatan ini adalah pelatihan dengan demonstrasi dan diskusi serta pendampingan praktik. Kegiatan pengabdian dilaksanakan di Kabupaten Banyuwangi dengan peserta guru Pendidikan Jasmani Olahraga dan Kesehatan. Melalui kegiatan ini, Fakultas Ilmu Keolahragaan dan Kesehatan Universitas Negeri Surabaya dapat memberikan nilai guna yang positif dalam bentuk kegiatan pengabdian untuk meningkatan sumber daya manusia dan mitra. Respon peserta terkait pelaksanaan kegiatan yaitu dengan rata-rata penilaian 4.4 dari rentang 0-5. Kata Kunci: pelatihan; pertolongan pertama; guru pendidikan jasmani